Preparation, characterization and evaluation of a novel CMC/Chitosan-α-Fe2O3 nanoparticles-coated 17-4 PH stainless-steel foam - Karakus, Selcan; Albayrak, Inci; Ullen, Nuray Bekoz; Insel, Mert Akin; Kilislioglu, Ayben (SPRINGER, 2022)
In this study, we fabricated a novel CMC/Chitosan-alpha-Fe2O3 nanoparticles (NPs)-coated 17-4 PH stainless-steel foam. The CMC/Chitosan matrix was preferred as a stabilizing role in the uniform dispersion of alpha-Fe2O3 NPs in the colloidal solution. The BET, SEM/EDX, XRD, and FT-IR techniques were used to determine the functional groups and surface of the nanostructure. The alpha-Fe2O3 NPs were uniformly dispersed and had a spherical shape with an average particle size of 10-20 nm with a surface area of 180.37 m(2)/g. Additionally, we examined to identify the physicochemical properties of the alpha-Fe2O3 NPs under ultrasonic irradiation. According to SEM results, we found that the average particle size of CMC/Chitosan-alpha-Fe2O3 NPs was between 10 and 20 nm with a spherical shape. We observed the effects of the operating parameters such as the concentration (0-1 ppm), mass fraction (10-20%) of silica, mass fraction (1-5%) of CTAB, temperature (25-45 degrees C), pH (3-10), sonication time (5-20 min), and the amplitude of sonication (10-40%). A mathematical modeling was performed, which related surface tension via the operating variables. The critical micelle concentrations were found 0.399, 0.428, and 0.573 ppm for mass fractions 10, 15, and 20% of silica, respectively. An error analysis was conducted in order to evaluate the physicochemical properties of the constructed models. Results showed that the effect of ultrasonic irradiation on the surface tension of biopolymer blend based alpha-Fe2O3 NPs and the design of uniform stainless-steel foam with alpha-Fe2O3 NPs coatings.
Keywords: Α -Fe2O3 nanoparticles; Surface tension; Chitosan; Biopolymer; IRON-OXIDE NANOPARTICLES; SURFACE MODIFICATION; TENSION; Polymer Science